4-Hydroxy-N′-(2-hydroxy-3-methoxybenzylidene)benzohydrazide monohydrate - Lu, Jiu-Fu (International Union of Crystallography, 2008)
In the title compound, C(15)H(14)N(2)O(4)·H(2)O, the dihedral angle between the two aromatic rings is 33.3 (5)°. The methoxy group is twisted slightly away from the attached benzene ring [C—O—C—C = 13.8 (9)°]. An intramolecular O—H⋯N hydrogen bond is observed. In the crystal structure, the molecules are linked into a two-dimensional network parallel to the (010) plane by intermolecular N—H⋯O, O—H⋯O and C—H⋯O hydrogen bonds